A letter of Abilpeiz Sultanto the military governor of Yili and its Manchu translation (Eurasian Journal of Philology Science and Education, 2019)
This paper utilizes a historical-philological approach toexamine one by one a letter written byAbilpeiz to the military governor of Yili in 1775 for his father-in-law Bozuk and the Oyirad womanwho fled with her children, and its Manchu translation, including its Latin transcription and modernKazakh translation. Furthermore, these documents elucidate the literary significance and linguisticcharacteristics of Kazakh history, language and culture and Kazakh-Oyirad relations. It was the firstattempt to study letters in diachronous terms, to study the history of the Kazakh literary language of theeighteenth century using archival materials with translations into Manchurian and Kazakh languages. Inthe article of the letter, the Abilpeiz of the Sultan is considered as a folk culture as a whole and isstudied in conjunction with the customs, rites and beliefs of both the distant ancestors of the Kazakhsand the Kazakh ethnos proper. It was this approach that determined the structure and purpose of thearticle, which allowed us to show the genesis and evolution of the genres of epistolary writing from theearliest, syncretic forms to full-fledged art formations, to reveal the ancient foundations of classicalplots and motifs.